Fuzzy Treatment of Candidate Outliers in Measurements - Giampaolo E. D'Errico; Nadir Murru (Advances in Fuzzy Systems)
Robustness against the possible occurrence of outlying observations is critical to the performance of a measurement process. Open questions relevant to statistical testing for candidate outliers are reviewed. A novel fuzzy logic approach is developed and exemplified in a metrology context. A simulation procedure is presented and discussed by comparing fuzzy versus probabilistic models.